Formation of bubbles and blisters in hydrogen ion implanted polycrystalline tungsten. Issue 11 (2nd December 2018) - Zhang, Jiandong; Zhao, Jiangtao; Jiang, Weilin; Guan, Xingcai; Peng, Haibo; Zhu, Zihua; Wang, Tieshan
ABSTRACT: Tungsten (W) has been regarded as one of the most promising plasma facing materials (PFMs) in fusion reactors. The formation of bubbles and blisters during hydrogen (H) irradiation will affect the properties of W. The dependence of implantation conditions, such as fluence and energy, is therefore of great interest. In this work, polycrystalline tungsten samples were separated into two groups for study. The thick samples were implanted by 18 keV H3 + ions to fluences of 1 × 10 18, 1 × 10 19 and 1 × 10 20 H + /cm 2, respectively. Another thick sample was also implanted by 80 keV H2 + ions to a fluence of 2 × 10 17 H + /cm 2 for comparison. Moreover, the thin samples were implanted by 18 keV H3 + ions to fluences of 9.38 × 10 16, 1.88 × 10 17 and 5.63 × 10 17 H + /cm 2, respectively. Focused ion beam (FIB) combined with scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used for micro-structure analysis, while time-of-flight ion mass spectrometry (ToF-SIMS) was used to characterize the H depth profile. It is indicated that bubbles and blisters could form successively with increasing H + fluence. H bubbles are formed at a fluence of ∼5.63 × 10 17 H + /cm 2, and H blisters are formed at ∼1 × 10 19 H + /cm 2 for 18 keV H3 + implantation. On the other hand, 80 keV H2 + ions can create more trapping sites in a shallow projected range, and thus enhancing the blisters formation with a relatively lower fluence of 2 × 10 17  H + /cm 2 . The crack-like microstructures beneath the blisters are also observed and prefer to form on the deep side of the implanted range.